2005
DOI: 10.1098/rsif.2005.0102
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of hyperactivity, impulsivity and cognitive diversity

Abstract: The evolutionary status of attention deficit/hyperactivity disorder (ADHD) is central to assessments of whether modern society has created it, either physically or socially; and is potentially useful in understanding its neurobiological basis and treatment. The high prevalence of ADHD (5-10%) and its association with the seven-repeat allele of DRD4, which is positively selected in evolution, raise the possibility that ADHD increases the reproductive fitness of the individual, and/or the group. However, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 130 publications
1
77
0
Order By: Relevance
“…Two of these articles report results from genetic studies (23,31), and one reports a computational simulation study (32) The 7R was associated with ADHD in a meta-analysis of candidate gene studies (33), but the odds ratio was low (only 1.3). Furthermore, DRD4 has not yet been implicated by genome-wide association studies (34) and current thinking is that ADHD susceptibility is influenced by many common and rare variants (9).…”
Section: Discussionmentioning
confidence: 99%
“…Two of these articles report results from genetic studies (23,31), and one reports a computational simulation study (32) The 7R was associated with ADHD in a meta-analysis of candidate gene studies (33), but the odds ratio was low (only 1.3). Furthermore, DRD4 has not yet been implicated by genome-wide association studies (34) and current thinking is that ADHD susceptibility is influenced by many common and rare variants (9).…”
Section: Discussionmentioning
confidence: 99%
“…To be clear while it has been 150 years since Darwin in his works suggested the possibility of a survival gene ('Sympatin' gene) it is proposed herein that the gene referred to be Darwin could be related to the DRD2 A1 allele. However this polymorphism (rs1800497) resides in the ANKK1 gene which interacts with the biological activity of DRD2 receptor [11][12][13] (also seehttp://www.ncbi.nlm. nih.gov/SNP/snp_ref.cgi?rs=1800497).…”
Section: Mapping Survival--like Behaviours and Dopaminergic Activitymentioning
confidence: 99%
“…Over 150 years later, this hypothesis is that the 'Sympatin' gene maybe the Taq AI allele a variant of the dopamine D2 receptor (DRD2) gene. In genetic studies the Taq AI allele a variation has been associated with a number of survival-like behaviours [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Specially, Williams and Taylor state that, "we have suggested two advantages of ADHD-HI to society: first, increased exploration of behavioral possibilities and second, the confining of concomitant social and physical risk to a minority" (p. 408). 24 Although some studies have indicated that there is no significant difference in creativity between those with ADHD and those without ADHD, 25 it is our suggestion that more research must be done to investigate this phenomenon specifically among the engineering students with ADHD. The present study attempts to discover a similar trend by using the Brown ADD Scales for Adults and Torrance Test of Creative Thinking (TTCT) Figural Form A.…”
Section: Creative Potential Of Individuals With Adhd Characteristicsmentioning
confidence: 99%